Perancangan Otentikasi One Time Password menggunakan Kode Unik via Email - Erna Kumalasari Nurnawati (Jurnal Dinamika Informatika, 2023)
The use of usernames and passwords as authentication requirements on a system that is used repeatedly can make account security on the system vulnerable to data theft. One of the methods to avoid authentication data theft is the One Time Password (OTP) technique, which uses a key that is temporary and will disappear after a while or after use.. In this research, the OTP code sent will be used as an OTP key and password replacement to authenticate to the system. This research method uses waterfall which has stages such as: a) Data Collection; b) Algorithm and Application Design; c) Coding or Implementation; d) Testing; e) Deployment. This study presents how the application workflow, web service routing and database design are used.. The test results in this study went well and according to the algorithm design and the formulated application workflow where users can authenticate the system using email and OTP codes instead of passwords.. The OTP code can be sent by the web service and received by the user. This research is expected to contribute to system security by authentication using a unique code as a substitute for a password that users receive via e-mail registered in the database.